2007
DOI: 10.1086/520016
|View full text |Cite
|
Sign up to set email alerts
|

Throat Swabs Are Necessary to Reliably Detect Carriers of Staphylococcus aureus

Abstract: The anterior nares are the most important screening site of colonization with Staphylococcus aureus. We screened 2966 individuals for S. aureus carriage with swabs of both nares and throat. A total of 37.1% of persons were nasal carriers, and 12.8% were solely throat carriers. Screening of throat swabs significantly increases the sensitivity of detection among carriers by 25.7%.The anterior nares are considered to be the primary colonization site of Staphylococcus aureus [1][2][3]. Approximately 30% of the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
169
3
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 211 publications
(199 citation statements)
references
References 11 publications
19
169
3
8
Order By: Relevance
“…The strength of our study is the unique environment of the hospital: less than 0.5% of all patients admitted to the hospital are colonized with MRSA, as reported by Mertz et al [21] and confirmed by a recent screening of 1,000 patients on admission (data not shown). In addition, the surveillance program identifies only between 2 and 10 transmissions per year in our 750-bed tertiary care hospital.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The strength of our study is the unique environment of the hospital: less than 0.5% of all patients admitted to the hospital are colonized with MRSA, as reported by Mertz et al [21] and confirmed by a recent screening of 1,000 patients on admission (data not shown). In addition, the surveillance program identifies only between 2 and 10 transmissions per year in our 750-bed tertiary care hospital.…”
Section: Discussionsupporting
confidence: 63%
“…In our setting, the low incidence of MRSA coupled with a prospective active screening program using a standardized case report form provided a unique opportunity to classify MRSA patients with epidemiological data and results from molecular typing [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The farms investigated were a representative sample of The Netherlands by region and type of farm, although the response rate (47 %) may have caused a bias for farms cooperating because of previous knowledge on MRSA (and an interest in participating) or no knowledge (and no fear of participating). Nasal sampling is known to identify the majority of MRSA carriers [27]. Visits were spaced and samples carefully handled to avoid crosscontamination from one farm to another.…”
Section: Discussionmentioning
confidence: 99%
“…Vis dėlto S. aureus aptinkamas ir kaip komensalinis mikroorganizmas žmonių šnervėse bei ryklėje [1,2]. Beveik 20 proc.…”
Section: įVadasunclassified